SPIRITUAL EDUCATION THROUGH THE DEVELOPMENT OF READING CULTURE IN EDUCATIONAL INSTITUTIONS OF SURKHANDARYA REGION (PROBLEMS, SOLUTIONS AND PROSPECTS) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This scientific article is devoted to the topical issues of improving the spiritual education of youth through the development of reading culture in educational institutions of Surkhandarya region. Also, the material and technical base and the composition of the library of 30 educational institutions were studied in depth. The article scientifically substantiates the impact of reading culture on such indicators as youth's worldview, moral qualities, sense of patriotism, respect for national and universal values, and social activity. As a result of the study, the current state of reading culture in educational institutions of the region, existing problems were systematized, and strategic directions, innovative approaches and practical mechanisms for their elimination were developed.